Universal rights from external reasons. - Schaefer, Brian (The University of Edinburgh. College of Humanities and Social Science, 2002)
The thesis is an attempt to find a satisfactorv grounding for universal moral rights. It attempts to ground universal moral rights in a revised version of the framework of moral reasons offered by T.M. Scanlon in What We Owe to Each Oflzer. In doing so it takes on several related projects. It makes a case for why rights generally, and universal rights in particular, are an essential part of a proper moral theory. It then attempts an extended argument in support of why the method of grounding universal rights at which I eventuallv arrive is superior to competitors. The argument encompasses both why I believe that universal rights need to be grounded in an objective meta-ethcs, and why I take the sort of irrealist cognitivism advanced by Scanlon to be the most promising form of moral objectivism. The argument is admittedly defeasible: it is not so ambitious as to try to eliminate every competing rights theory, but it purports to be strong enough to show that my theory enjoys significant adivantages over manv others. In the course of making this argument I align myself with the natural law tradition, and claim that mv position is best understood as a new natural law theory. The thesis goes on to defend many elements of the Scanlonian picture of moral reasons, but also to revise that picture in important ways, particularly by arguing that Scanlon’s contractualism is best understood to be underpinned bv an account of the sacred offered by Ronald Dworkin, and that some moral reasons are reasons we all share. The final chapter of the thesis shows how rights are derived from Scanlonian reasons, and particularly how universal rights are derived from shared reasons.
Keywords: universal moral rights, moral theory, moral reasons, shared reasons